Enolases: Limitations for Implementation in Clinical Practice (Critical Review) - A. М. Golubev (Общая реаниматология, 2024)
Enolases (ENOs) are involved in glycolysis, which is critical for providing energy to cells under hypoxic conditions. ENOs are attracting the attention of researchers as a potential diagnostic marker for critical conditions.The aim of this review is to analyze the reasons limiting the clinical use of ENOs for diagnostic and prognostic purposes in critical conditions.We selected and analyzed 87 publications in which ENOs assessment was mainly performed in patients with critical illness. Criteria for selecting relevant publications from PubMed and Elibrary were based on a presence of authors' recommendations or current guidelines on clinical use of ENOs for diagnostic or prognostic purposes.Specific properties of human ENO isoenzymes were reviewed, clinical aspects and recommendations for their clinical use, as well as methodological and procedural errors in ENO testing were considered.The following controversial issues were identified: the measured level of ENOs does not characterize the true enzymatic activity of their numerous molecular isoforms; identification of specific ENO isoforms using antibodies to structural subunits does not allow assessment of the true content and enzymatic activity of potentially circulating isoenzymes (e.g., gamma-gamma and alpha-gamma ENOs); the concept of cell specificity ascribed to heterodimers (in particular, gamma-alpha enolase is considered to be neuron-specific) is not supported by the results of the available studies, since this heterodimeric form of ENO is present in a variety of human tissues; some procedural issues are not taken into account (e.g., latent hemolysis, lack of standardized assessment methods, etc.).Conclusion. The use of advanced diagnostic platforms based on the assessment of the content and enzymatic activity of each ENO isoform should provide valuable information on their specific role in the pathogenesis of diseases in the context of personalized medicine and will enable the evaluation of their diagnostic and prognostic significance, as well as the effectiveness of therapeutic interventions.